Attitudes of EFL Students towards English Language Learning: A Study at the College of Arts, University of Kufa - Al-Muslimawi, Ihssan Abdulkadhum Jabor; Al-Shamarti, Abdullah Kareem (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The aim of this study is to examine the attitudes of EFL students. A person's attitude is their response to such situations. Attitudes can be behavioural, cognitive, or emotional. The instrument used in this analysis is a 21-item questionnaire. A total of 120 students were asked to complete the survey accurately. They are in various academic years, age classes, and English proficiency standards. The findings show that there are major variations in the students' attitudes. The findings also indicate that learners' attitudes are influenced by their gender. Moreover, the results reinforce that the year of study has an effect on students' attitudes. Age can also make a significant difference on the learners’ attitudes.